Examining the sustainability of teacher learning following a year-long science professional development programme for inservice primary school teachers. Issue 3 (27th May 2017) - Drits-Esser, Dina; Gess-Newsome, Julie; Stark, Louisa A.
Abstract : This two-year, mixed-methods study explored teacher learning during a year-long professional development programme and during the year following the programme. The study examined patterns of change in primary school teachers' inquiry practices, inquiry beliefs and physical science content knowledge during both years as well as the effects of school-level and individual-level factors on these changes in the year following the programme. Fifteen fourth-grade through sixth-grade teachers from three low-performing US schools participated. Results indicated that the programme was effective in advancing teacher change during the programme year, as scores in all three measures increased at statistically significant rates. Only content knowledge scores increased significantly in the year following the professional development. A combination of school-level and individual-level factors impacted the year 2 changes. School-level factors were: having supportive same-grade teams and/or a supportive mentor who advocated inquiry science and who prioritized science as a subject; principal prioritization of science; and having easy access to and training in the use of relevant materials. The primary individual-level factor was the degree of teachers' willingness and readiness to change beliefs in fundamental ways. Implications for professional development providers and school administrators are discussed.